1998
DOI: 10.1002/hep.510280428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon therapy on hepatitis C virus RNA in whole blood, plasma, and peripheral blood mononuclear cells

Abstract: Fifty-two patients with chronic hepatitis C virus (HCV)infection were treated with standard doses of interferon alfa-2b. During treatment, HCV RNA detection was studied in samples of whole blood (WB), plasma (Pl), and peripheral blood mononuclear cells (PBMCs). Individuals were classified as sustained responders (SRs), complete responders with relapse (CRs), partial responders (PRs), or nonresponders (NRs) according to normalization of serum alanine transaminase (ALT) during treatment and follow-up. Before tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
(70 reference statements)
2
31
0
Order By: Relevance
“…Schmidt and colleagues have investigated the distribution of HCV in whole blood and in the different cell fractions. Whole blood contained significantly more HCV-RNA than pasma, which contained more HCV-RNA than PBMC, the lowest level of HCV-RNA was found in granulocytes and in red blood cells/pellets [13,14] . In the case of granulocytes, the virus may simply be ingested by phagocytosis and in the red blood cells or pellets.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Schmidt and colleagues have investigated the distribution of HCV in whole blood and in the different cell fractions. Whole blood contained significantly more HCV-RNA than pasma, which contained more HCV-RNA than PBMC, the lowest level of HCV-RNA was found in granulocytes and in red blood cells/pellets [13,14] . In the case of granulocytes, the virus may simply be ingested by phagocytosis and in the red blood cells or pellets.…”
Section: Discussionmentioning
confidence: 90%
“…It has been hypothesized that virus replication takes place at extrahepatic sites. Possible sites are the different cell fractions (PBMC, granulocytes or red blood cells/pellets) of the peripheral blood [13,14] or tissues like lymph nodes, pancreas, adrenal gland thyroid, bone marrow or spleen [15] . In particular, PBMCs have been suggested to function as an important extrahepatic reservoir or as a possible site for e x t r a h e p a t i c H C V r e p l i c a t i o n [ 1 6 -1 9 ] .…”
Section: Introductionmentioning
confidence: 99%
“…103 Thus, it is provocative to speculate that low-level replication of HCV in PBMCs may lead to reactivation of HCV after termination of therapy and/or predict response to therapy. 80,99,100,[102][103][104][105] As reviewed elsewhere, HCV is likely involved in several neurologic syndromes. 16 While central nervous system (CNS) involvement is less frequent, the detection of negative-strand HCV RNA in the CNS 29 suggests a potential link between HCV and these extrahepatic pathol- ogies.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
“…Our study of 115 patients with HCV infection demonstrated that the improved sensitivity of whole-blood HCV RNA detection correlated with the presence and quantity of cryoglobulins (8). We also noted highly significant differences in the detection of HCV RNA for whole blood and plasma among 52 interferon-treated patients who were monitored throughout treatment (7). As was the case for the one patient studied by Cook et al (3), among our 52 patients the clearance of intracellular virus occurred nearly simultaneously with the clearance of plasma virus during therapy (7).…”
Section: Whole-blood Hepatitis C Virus Rna Extraction Methodsmentioning
confidence: 56%
“…We read the article by Cook et al (3) with interest, since they compared their findings with our previous work (4)(5)(6)(7)(8) (3,4). (iv) Finally, the serum volume was not adjusted to the whole-blood volume (3), which we took into account (6).…”
Section: Whole-blood Hepatitis C Virus Rna Extraction Methodsmentioning
confidence: 99%